APOGEE detection of N-rich stars in the tidal tails of Palomar 5. Issue 3 (4th December 2021) - Phillips, Siân G; Schiavon, Ricardo P; Mackereth, J Ted; Allende Prieto, Carlos; Anguiano, Borja; Beaton, Rachael L; Cohen, Roger E; García-Hernández, D A; Geisler, Douglas; Horta, Danny; Jönsson, Henrik; Kisku, Shobhit; et al.
ABSTRACT: Recent results from chemical tagging studies using Apache Point Observatory Galactic Evolution Experiment data suggest a strong link between the chemical abundance patterns of stars found within globular clusters (GC), and chemically peculiar populations in the Galactic halo field. In this paper, we analyse the chemical compositions of stars within the cluster body and tidal streams of Palomar 5, a GC that is being tidally disrupted by interaction with the Galactic gravitational potential. We report the identification of nitrogen-rich (N-rich) stars both within and beyond the tidal radius of Palomar 5, with the latter being clearly aligned with the cluster tidal streams; this acts as confirmation that N-rich stars are lost to the Galactic halo from GCs, and provides support to the hypothesis that field N-rich stars identified by various groups have a GC origin.